Firearms, the law, and forensic ballistics - Warlow, T. A. (Boca Raton, Fla. : CRC Press, 2005)
Featuring new and updated information, Firearms, the Law, and Forensic Ballistics, Second Edition offers a comprehensive reference on the forensic science of firearms. The book begins with an overview of firearm development, and then explores firearm law around the world, as well as the pioneers and principles of the new science of forensic ballistics. Allowing a closer look at the operation of modern weapons, the text includes a review of ballistics and explains the role of the ballistics expert. The book also provides guidance on laboratory techniques, setting up databases, the recovery of deleted markings and serial numbers, and the presentations of evidence in court.--Jacket.
The beginnings -- Firearms legislation and the definition of a firearm -- Marks and microscopy: the emergence of a new science -- Manufacture, mechanisms, and design aspects of firearms -- Internal ballistics -- External ballistics and cartridge loadings -- Terminal/wound ballistics and distance of firing -- The scene of the shooting incident -- Examination of exhibits at the laboratory -- Presentation of evidence to the courts -- Proof marks and the proof of firearms -- Appendix 1: Useful data -- Appendix 2: German ordnance codes used between 1938 and 1945.
Includes bibliographical references and index.
Keywords: Featuring new and updated information, Firearms, the Law, and Forensic Ballistics, Second Edition offers a comprehensive reference on the forensic science of firearms. The book begins with an overview of firearm development, and then explores firearm law around the world, as well as the pioneers and principles of the new science of forensic ballistics. Allowing a closer look at the operation of modern weapons, the text includes a review of ballistics and explains the role of the ballistics expert. The book also provides guidance on laboratory techniques, setting up databases, the recovery of deleted markings and serial numbers, and the presentations of evidence in court.--Jacket.; Forensic ballistics; Forensic ballistics